Bach2 Deficiency Leads to Spontaneous Expansion of IL-4-Producing T Follicular Helper Cells and Autoimmunity - Zhang, Heng; Hu, Qianwen; Zhang, Min; Yang, Fang; Peng, Cheng; Zhang, Zhen; Huang, Chuanxin (Frontiers in Immunology, 2019)
The transcription factor Bach2 is a susceptible gene for numerous autoimmune diseases including systemic lupus erythematosus. Bach2-/- mice can develop a lupus-like autoimmune disease. However, the exact cellular and molecular mechanisms via which Bach2 protects the hosts from developing autoimmunity remains incompletely understood. Here, we report that Bach2 ablation on T cells, but not B cells, resulted in humoral autoimmunity, and this was associated with expansion of T follicular helper (Tfh) cells and abnormal germinal centers. Bach2 was down-regulated in Tfh cells, and directly suppressed by the Tfh-defining transcription factor BCL6. Mechanistically, Bach2 directly suppresses the transcription of Cxcr5 and c-Maf, two key regulators of Tfh cell differentiation. Bach2-deficient Tfh cells were skewed towards IL-4-producing subset, which induced IgG1 and IgE isotype switching of B-cells. Heterozygous Bcl6 deficiency reduced the formation of germinal center and autoantibodies, and ameliorated the pathology in Bach2-deficient mice. Our findings identify Bach2 as a crucial negative regulator of Tfh cells at steady state, and prove that Bach2 controls autoimmunity in part by restraining accumulation of pathogenic Tfh cells.